KUASA AKTOR DALAM “DUNIA” PARKIR LIAR (Studi Kasus Kuasa Aktor dalam ‘Dunia’ Parkir Liar di Sekitar RSUP Dr. Sardjito dengan menggunakan Perspektif Foucauldian dan Gramscian) - Agusniar Rizka Luthfia (Cakrawala Jurnal Penelitian Sosial, 2015)
This research aims to find the role of power-actor in the illegal parking underworld around RSUP Dr. Sardjito area. By utilizing Gramscian and Foucauldian discourse analysis, this qualitative research with purposive sampling technique was able to reveal some findings: the power-actor in the illegal parking syndicate around RSUP Dr. Sardjito has been using their influence to establish illegal parking community, as well as its unwritten rules and regulations. The power-actor has the control over the distribution of the parking plots and they decide on who can allowed to work as illegal parking attendants, as well as to assign supervisors –whose role is to initiate and enforce the rules necessary to bind the community together and to protect its existence.Keywords: Illegal Parking, Gramscian, Foucauldian, Power-actor.